Muslim Thoughts in Facing Globalization in Contemporary Times - Muhammad Adhil Fatih Nasrullah; Lina Pusvisasari (Penerbit Hellow Pustaka, 2025)
This research focuses on the history of Islam in the contemporary era, especially on the role of Islam in world civilization, both regarding ethics and aesthetics. Islamic globalization is a phenomenon that describes how Islam interacts and adapts to the globalization process which involves the movement of ideas, people and culture in a global context. This process has had a significant impact on the development of Islamic thought, where globalization has triggered the emergence of various Islamic movements, such as modernist, fundamentalist revivalist and transformative Islam. Where each movement responds in a different way to the globalization process. For example, the modernist movement tends to be open to change and innovation by emphasizing rationalism, reform and tolerance. Meanwhile, fundamentalist revivalists tend to be reactive and want to maintain tradition. Meanwhile, transformative Islam tries to find a middle way by combining traditional and modern values, so that Islam can become a relevant and relevant religion for humanity in the future. The author uses a qualitative approach from relevant sources.